«Зачарована Десна» як компендіум автобіографічних мотивів прози Олександра Довженка - Констанкевич, Ірина; Konstankevych, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто кіноповість «Зачарована Десна» в контексті автобіографічного дискурсу, проаналізо-вано жанрові й стильові особливості художньої автобіографії. Зосереджено увагу на автопсихоаналічній функції, двоплановості часової організації тексту./ In the article kinopovist “Zacharovana Desna” is viewed in the context of autobiographical discourse, genre and stylistic pecularities of artistic autobiography are analyzed. Attention is focused on the autopsychoanalytical function and duality of the temporal organization of the text. Autobiography was often provided as an unrecognized step child, literary criticism was unwillingly interested in because of its boundary status between guidance on reference, “truth of life” and regardless of the existing genre structure, speech figures and tropes. Thus in Socialist Realism, this genre was doubly marginalized. Some concepts in Socialist Realism were under threat, namely Modernist curriculum “introverted” subjectivity, focusing on individual, private experience, deep reflexivity. Most advanced creative method of Soviet literature aspired to didactic uniqueness incompatible with the search for meaning in the complexity of contemporary reality, and thus confession does not fit into the rigid regulatory scheme. The capacity for self-reflection (“self-analysis” in terms of ideological criticism supervisory) became rather negative character trait. So Soviet decades were extremely poor in autobiographical and memoir genre.
“Zacharovana Desna” as Compendim of Autobiographical Motives of Alexander Dovhenko’s Prose
Констанкевич І. «Зачарована Десна» як компендіум автобіографічних мотивів прози Олександра Довженка / Ірина Констанкевич // Науковий вісник Східноєвропейського національного університету. Сер. «Філологічні науки. Літературознавство». – 2014. – № 9 (286). – С. 73-77.
Keywords: автобіографічний текст; "автобіографія про дитинство"; автопсихоаналітична функція; часопростір; двоплановість; autobiographical text; “autobiography about childhood”; autopsychoanalytical function; timespace; duality